Prevalence of Musculoskeletal Injuries Among Factory Workers in Kano Metropolis, Nigeria - Adamu Saidu, Ismaila; Adimabua Utti, Victor; Olugbenga Jaiyesimi, Adeolu; Ahmad Rufa'i, Adamu; Monday Maduagwu, Stanley; Adezie Onuwe, Henry; Mohammed Jajere, Abdurahman (International journal of occupational safety and ergonomics, 2011)
Background. Kano is a metropolis and commercial centre in northern Nigeria; it is highly industrialized. Most of the population does factory work. Purpose. The survey was undertaken to identify the prevalence of musculoskeletal injuries (MSIs) and other related occupational hazards among factory workers in Kano Metropolis. Method. Five hundred questionnaires were distributed to respondents recruited from tannery, steel rolling, textile and agrochemical factories at the 3 industrial estates of the metropolis. Only unskilled and manual labourers were considered. The respondents were selected using the nonprobability sample of convenience. Results. Only 420 questionnaires were returned duly completed. Three hundred and fifty-three (84.05%) respondents were male and 67 (15.95%) were female. Their ages ranged between 21 and 58 years (M = 38.99 ± 1.01). Results. Low back complaints had the highest prevalence (360, 85.71%), followed by upper limb injuries (171, 40.71%), shoulder complaints (156, 37.14%) and hip injuries (34, 8.10%). About 41% of the respondents reported 2 or more work-related MSIs. Conclusion. The study uncovered that a substantial percentage of factory workers had sustained MSIs. Body ache/discomfort in the low back region was the most common injury sustained among the subjects surveyed.